Proving the Crime of Witchcraft in Syariah Court In Malaysia: Issues and Challenges - Muhammad Hafiy Irfan Mohammad; Amalina Ahmad Tajudin (USIM Press, 2025)
This study provides an abstract survey on the crime of witchcraft in Malaysia, especially in relation to the issues and challenges of proving the crime in the Syariah Court in Malaysia. One of the main challenges found in this study is that the jurisdiction that manages and handles witchcraft-related crimes in Malaysia is still not yet been established. Furthermore, the research problem that exists is related to the guidelines for convicting witchcraft in Syariah courts. Therefore, challenges arise in determine the parameters of the extent to which an offense is identified as a crime of witchcraft. Based on this research, there are several objectives to be achieved, among them are to identify the positive effects of the enactment of laws, Investigating the process of proving the crime of witchcraft in Syariah Court, analyse the issues and challenges in proving the crime of witchcraft and also examining their solutions to address them. This study also uses qualitative methods in obtaining information. While the findings for this study are benefits of witchcraft law, process of proving the crime, challenges in proving the crime of witchcraft and solutions to address issues and challenges. The conclusion that can be made based on this study is that although this crime of witchcraft is a crime that is difficult to prove, it is not impossible to make it happen with joint efforts from various parties. The significant of this research are it can contribute to legal development, community protection and strengthen Syariah legal institutions in Malaysia. Therefore, it will contribute to international scholars in terms of the latest information and data related to witchcraft crimes in Malaysia, challenges and solutions in strengthening the witchcraft crime laws as well as ideas in the implementation of the special body regarding witchcraft crimes.